حديث الفتنة من قبل المشرق : شرحه ودراسته - Muhammad Rizal Bin Abdul Manaf (Kolej Universiti Islam Malaysia, 2011)
This research is a researching and analyzing towards several al-Hadith from Prophet Muhammad which related of existing "al-fitan min qibal al-masyriq". The purpose of this study is to find out what is the real term of al-fitan rise from east which state by Rasulullah S.A.W and to search what is the character, place which known as masyriq and when will it arise. Several technique been apply to seek the ensure of this study especially, takhrij hadith and dirasah asanid method. Furthermore, the related books be referred for analyze to gather more information. The result has proven al-fitan is including all the badness and destruction that can spread the Muslim and al-fitan also include the sign of hereafter, major or minor. The specific place of the al-fitan be risen can't be determine accurately. But the existing of al-fitan can be recognize from the murder of khalifa Usman base on majority of ulama' opinion.